Stratification in Al and Cu foils exploded in vacuum; Physics of Plasmas; Vol. 22, № 10 - Baksht R. B.; Rousskikh A. G.; Zhigalin A. S.; Oreshkin V. I. Vladimir Ivanovich; Artyomov A. P. (2015, 2015)
Title screen